Archive: Pushing boundaries? Challenging traditional gender roles in Kyle XY. (2nd April 2015) - Brown, Shane
Abstract : Kyle XY (US 2006-09) was a mix of sf and teen drama aimed not just at teenage audiences but also family audiences in general. Now almost forgotten, the programme can be seen as a missing link between series with a similar format, such as Roswell (US 1999-2002) and The Vampire Diaries (US 2009-). This article explores how successful the series was in pushing the boundaries of gender roles within the contexts of a family show.